Biocontrol and plant growth promoting traits of two avocado rhizobacteria are orchestrated by the emission of diffusible and volatile compounds - Elvis M. Cortazar-Murillo; Alfonso Méndez-Bravo; Juan L. Monribot-Villanueva; Edith Garay-Serrano; Ana L. Kiel-Martínez; Mónica Ramírez-Vázquez; Mónica Ramírez-Vázquez; Edgar Guevara-Avendaño; Alejandro Méndez-Bravo; José A. Guerrero-Analco; Frédérique Reverchon (Frontiers in Microbiology, 2023)
Avocado (Persea americana Mill.) is a tree crop of great social and economic importance. However, the crop productivity is hindered by fast-spreading diseases, which calls for the search of new biocontrol alternatives to mitigate the impact of avocado phytopathogens. Our objectives were to evaluate the antimicrobial activity of diffusible and volatile organic compounds (VOCs) produced by two avocado rhizobacteria (Bacillus A8a and HA) against phytopathogens Fusarium solani, Fusarium kuroshium, and Phytophthora cinnamomi, and assess their plant growth promoting effect in Arabidopsis thaliana. We found that, in vitro, VOCs emitted by both bacterial strains inhibited mycelial growth of the tested pathogens by at least 20%. Identification of bacterial VOCs by gas chromatography coupled to mass spectrometry (GC–MS) showed a predominance of ketones, alcohols and nitrogenous compounds, previously reported for their antimicrobial activity. Bacterial organic extracts obtained with ethyl acetate significantly reduced mycelial growth of F. solani, F. kuroshium, and P. cinnamomi, the highest inhibition being displayed by those from strain A8a (32, 77, and 100% inhibition, respectively). Tentative identifications carried out by liquid chromatography coupled to accurate mass spectrometry of diffusible metabolites in the bacterial extracts, evidenced the presence of some polyketides such as macrolactins and difficidin, hybrid peptides including bacillaene, and non-ribosomal peptides such as bacilysin, which have also been described in Bacillus spp. for antimicrobial activities. The plant growth regulator indole-3-acetic acid was also identified in the bacterial extracts. In vitro assays showed that VOCs from strain HA and diffusible compounds from strain A8a modified root development and increased fresh weight of A. thaliana. These compounds differentially activated several hormonal signaling pathways involved in development and defense responses in A. thaliana, such as auxin, jasmonic acid (JA) and salicylic acid (SA); genetic analyses suggested that developmental stimulation of the root system architecture by strain A8a was mediated by the auxin signaling pathway. Furthermore, both strains were able to enhance plant growth and decreased the symptoms of Fusarium wilt in A. thaliana when soil-inoculated. Collectively, our results evidence the potential of these two rhizobacterial strains and their metabolites as biocontrol agents of avocado pathogens and as biofertilizers.